The Relationship Of Knowledge With The Attitude Of Pregnant Women About The Benefits Of Folic Acid At Haji Medan Hospital - Hrp, Fitri Aidani Ulfa (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
This study is entitled the relationship of knowledge with attitudes of pregnant women about the benefits of folic acid. In general, this study aims to find out the picture of knowledge of pregnant women about the benefits of folic acid, and specifically this study aims to find out the picture of knowledge of pregnant women about the benefits of folic acid based on age, education, occupation, and sources of information. This type of research is descriptive research. This research was conducted at Haji Medan hospital. The population in this study was 30 pregnant women and the entire population was sampled in this study. A total of 20 questionnaires were distributed to respondents. And from the results of data analysis found the results of research that showed: The level of knowledge of mothers about giving folic acid in general is categorized as quite good. Maternal knowledge about folic acid administration based on the age of the majority of mothers aged 20-35 years with sufficient knowledge categories as many as 7 respondents (23.33%) and the minority of mothers aged >35 years with less knowledge categories as many as 1 respondent (3.33%) Maternal knowledge about folic acid administration based on the education of the majority of mothers with junior high school education levels with sufficient knowledge categories as many as 7 respondents (23.33%) and the minority of mothers with elementary school education with categories Good knowledge as much as 1 respondent (3.33%). Mothers' knowledge about folic acid administration based on the work of the majority of mothers with housewives work with good knowledge category as many as 7 respondents (23.33%) and the minority of mothers with housewife work also with good knowledge category as many as 2 respondents (6.67%). Mothers' knowledge about folic acid administration based on information sources, the majority of mothers with information sources from print/advertising media with sufficient knowledge categories as many as 7 respondents (23.33%) and the minority of mothers with information sources from neighbors with good and sufficient knowledge categories as many as 1 respondent each (3.33%).